Neuropeptide S Receptor as an Innovative Therapeutic Target for Parkinson Disease - Victor A. D. Holanda; Julia J. Didonet; Manara B. B. Costa; Adriano H. do Nascimento Rangel; Edilson D. da Silva; Elaine C. Gavioli (MDPI AG, 2021)
Parkinson disease (PD) is a neurodegenerative disease mainly characterized by the loss of nigral dopaminergic neurons in the substantia nigra pars compacta. Patients suffering from PD develop severe motor dysfunctions and a myriad of non-motor symptoms. The treatment mainly consists of increasing central dopaminergic neurotransmission and alleviating motor symptoms, thus promoting severe side effects without modifying the disease's progress. A growing body of evidence suggests a close relationship between neuropeptide S (NPS) and its receptor (NPSR) system in PD: (i) double immunofluorescence labeling studies showed that NPSR is expressed in the nigral tyrosine hydroxylase (TH)-positive neurons; (ii) central administration of NPS increases spontaneous locomotion in naïve rodents; (iii) central administration of NPS ameliorates motor and nonmotor dysfunctions in animal models of PD; (iv) microdialysis studies showed that NPS stimulates dopamine release in naïve and parkinsonian rodents; (v) central injection of NPS decreases oxidative damage to proteins and lipids in the rodent brain; and, (vi) 7 days of central administration of NPS protects from the progressive loss of nigral TH-positive cells in parkinsonian rats. Taken together, the NPS/NPSR system seems to be an emerging therapeutic strategy for alleviating motor and non-motor dysfunctions of PD and, possibly, for slowing disease progress.